Inovasi Produk Sabun Cuci Tangan Cair dan Sabun Kertas dari Garam Laut sebagai Upaya Peningkatan Kesehatan dan Mendukung Kewirausahaan - Octavina, Chitra; Nurfadillah, Nurfadillah; Fachri, Rania Feranita; Akbar, Said Ali; Arisa, Iko Imelda; Dewiyanti, Irma; Ulfah, Maria (Universitas Pendidikan Nasional, 2025)
Hand hygiene is a simple thing that is often overlooked, especially in schools located in coastal areas with limited sanitation facilities. This community service activity aims to introduce innovations in the production of liquid hand soap and sea salt-based paper soap as an effort to improve health and empower the local economy. The implementation methods include education, demonstrations of production, and direct training for community partners. This service was carried out at Banda Aceh State Elementary School 61 from July to September 2025. The training produced 30 L of liquid soap and 1000 sheets of paper soap; by the end of the session, 75% of participants completed all production steps correctly (checklist). Entrepreneurial outputs included a student–teacher sanitation team and two product mock-ups with basic costing (estimated unit cost Rp 12.000 per 500 mL vs market price Rp 18.000). These results indicate technical feasibility and school-based micro-enterprise potential. For sustainability, the school committed to monthly in-house production led by the sanitation team and integrating the activity into UKS to secure continuous supply and ongoing skill transfer.